THE EFFECT OF USING INSTAGRAM CAPTION ON STUDENTS’ VOCABULARY MASTERY AT TWELFTH GRADE OF SMA AL-AZHAR 3 BANDAR LAMPUNG. - Yanuar Dwi Prastyo; Zulkarnaen Zulkarnaen; Siti Farhana (Journal of English Educational Study (JEES), 2022)
Abstract: The phenomenon of Instagram users arising in Indonesia who shares about learning English independently, specifically learning vocabularies in this case Instagram caption, underlies this research to be studied profoundly. The objectives of the research were (1) to gain an overall picture of students’ vocabulary mastery in learning vocabulary through Instagram captions, (2) to find out students’ interest in learning vocabulary through Instagram. This journal used a mix-method. To collect the data used, vocabulary tests and interviews. The result showed that there was a statically significant difference between the students taught with the Instagram caption and the original way approach. It is revealed from the t-value, which is higher than the t-table with a significance level of less than 0.05. the result of the data, the researcher found the things that make students' interest in learning vocabulary through the Instagram captions. The data findings show that the majority of students are interested in learning vocabulary through Instagram because it was effective for them.Keywords: Instagram, Social Media, Caption, Vocabulary, Students’ interest.